Cytokine storm and sepsis disease pathogenesis - Chousterman, Benjamin G.; Swirski, Filip K.; Weber, Georg (Seminars in Immunopathology, 2017)
Infectious diseases are a leading cause of death worldwide. Sepsis is a severe clinical syndrome related to the host response to infection. The severity of infections is due to an activation cascade that will lead to an autoamplifying cytokine production: the cytokine storm. Cytokines are a broad category of relatively small proteins (<40 kDa) that are produced and released with the aim of cell signaling. Our understanding of the processes that trigger this tremendous amount of cytokine production has made dramatic progress over the last decades, but unfortunately, these findings could not translate yet into effective treatments; so far, all clinical trials targeting cytokine production or effects failed. This review aims to summarize the pathophysiology of the cytokine storm; to describe the type, effects, and kinetics of cytokine production; and to discuss the therapeutic challenges of targeting cytokines. New promising therapeutic strategies focusing on the endothelium, as a source and a target of cytokines, are described.
EVALuna2:15318